METHODOLOGY OF TEACHING ENGLISH AS A FOREIGN LANGUAGE - Toshpulatova Dilfuza Talgatovna (Galaxy International Interdisciplinary Research Journal, 2022)
Today, foreign language skills are becoming an integral part of vocational education. Specialists in various fields have a high level of cooperation with foreign partners, so they have a high demand for language learning. In modern society, foreign languages are becoming an important part of vocational education. Such knowledge is first acquired by people in schools, colleges, high schools, and later in institutes, training courses, or by familiarizing themselves with basic information sets that help them learn a foreign language independently. Today there is a large collection of teaching materials for people with different levels of language skills. Success in achieving this goal depends on the practical methods and skills of teachers. This article discusses the methods used to teach English as a foreign language.